Frontispiece: Low‐Temperature Cationic Rearrangement in a Bulk Metal Oxide. Issue 34 (9th August 2016) - Li, Man‐Rong; Retuerto, Maria; Stephens, Peter W.; Croft, Mark; Sheptyakov, Denis; Pomjakushin, Vladimir; Deng, Zheng; Akamatsu, Hirofumi; Gopalan, Venkatraman; Sánchez‐Benítez, Javier; Saouma, Felix O.; Jang, Joon I.; et al.
Abstract : Atomic‐Scale Engineering In their Communication onpage 9862 ff., M. Greenblatt et al. describe how a cationic rearrangement in Mn2 FeMoO6 at low temperature leads to an ordered ilmenite structzre with new magnetic and electrical properties.